Sediment yield and alternatives soil conservation practices of teak catchments - Tyas Mutiara Basuki (Journal of Degraded and Mining Lands Management, 2017)
Quantifying sediment is essential to determine its sources and reduce its negative impacts. A study was conducted to quantify suspended sediments of catchments covering by teak plantation and to provide alternatives soil conservation practices. Five catchments with old teak coverages of 82; 82; 74; 70; and 53 % were chosen. At the outlet of each catchment was installed tide gauge to monitor stream water level (SWL). Water samples for sediment analyses were taken for every increament of SWL. Sediment yield was calculated based on rating curves of sediment discharge. The results showed that the sources of sediment in the streams were dryland agricultural and streambank erosion. The mean annual sediment yield during the study were 9.3; 10; 15; 53.3; and 22.5 t/ha for catchments covered by old teak plantation of 82, 82, 74, 70, and 53 %, respectively. To reduce sediment yield some soil conservation practices must be applied. Conservation of soil organic matter is important in order to stabilize soil aggregate and prevent clay dispersion which causes erosion and sedimentation. Green firebreaks or making channels are needed to prevent fire during dry season and organic matter loss. Stabilization of streambank is neccesary, either using vegetative method or civil technics.